Electrochemical sensing and catalysis using Cu3(BTC)2 coating electrodes from Cu(OH)2 films. Issue 29 (3rd May 2017) - Okada, Kenji; Sawai, Shota; Ikigaki, Ken; Tokudome, Yasuaki; Falcaro, Paolo; Takahashi, Masahide
Abstract : Metal–organic framework (MOF) coatings were prepared on gold electrodes through the conversion from Cu(OH)2 nanobelts to Cu3 (BTC)2 MOFs. Abstract : Metal–organic framework (MOF) coatings were prepared on gold electrodes through the conversion from Cu(OH)2 nanobelts to Cu3 (BTC)2 MOFs (BTC = 1, 3, 5-benzenetricarboxylic acid). In the conversion from Cu(OH)2 to Cu3 (BTC)2, the porosity and homogeneity of the coatings are tunable by controlling the EtOH : H2 O volume ratio of the MOF precursor solution. The kinetics and mechanism of the conversion from metal hydroxide nanobelts to MOFs were investigated by using the quartz crystal microbalance (QCM) technique. The Cu3 (BTC)2 coatings were finally tested for the size-selective electrochemical sensing and non-enzymatic electrocatalysis of glucose.